Calibrating Time of Flight in Two Way Ranging - Baba, A. I. (2011 Seventh International Conference on Mobile Ad-hoc and Sensor Networks, 2011)
There has been a huge attention attracted by Wireless Sensor Network (WSN) applications in recent years. One of the significant part of these applications is "Localization". Nodes normally do not have any prior knowledge of their position when deployed. Thus a mechanism is required for nodes to determine their position. In this paper a new Two-Way Ranging (TWR) approach to find out the point-to-point range between the nodes is presented. The two way ranging technique can be prone to errors due to the delays associated with clock drift and low sampling frequency clock, thus may result in poor ranging accuracy. A new technique Two Way Ranging with Multiple Messages (TWR-MM) is introduced to remove such inaccuracies by calibrating the ranging nodes to achieve better ranging accuracy. The proposed solution is evaluated on a real test bed and using simulations. Results show accuracy within centimeters can be achieved, which is much better than simple TWR and Symmetrical Double Sided TWR (SDS-TWR).